Differences between adult sexual minority females and heterosexual females on menthol smoking and other smoking behaviors: Findings from Wave 4 (2016–2018) of the population assessment of tobacco and health study. (June 2022) - Ehlke, Sarah J.; Ganz, Ollie; Kendzor, Darla E.; Cohn, Amy M.
Highlights: Sexual minority females began smoking regularly earlier than heterosexuals. Sexual minority females were more likely to initiate with a menthol cigarette. Sexual minority females were more likely to be past 30-day smokers. Past 30-day menthol cigarette use was higher among sexual minority females. Abstract: Background: Sexual minority females have higher rates of cigarette smoking than heterosexual females. Additionally, menthol cigarette use disproportionately impacts minority smokers, including sexual minority individuals. This study examined differences between sexual minority and heterosexual females on several smoking variables, including initiation with a menthol cigarette, and past 30-day cigarette and menthol cigarette use. Methods: Participants were female ever smokers ( N = 11, 576; n = 1, 474, 12.7% sexual minority) who completed Wave 4 of the Population Assessment of Tobacco and Health Survey. Participants reported on the age they began smoking regularly (≤18 years old, 18–24, >25), whether they initiated with a menthol cigarette, past 30-day cigarette smoking and menthol cigarette use, cigarettes smoked per day (≤10, 11–20, >20), cigarette dependence (smoke ≤ 5 min of waking or > 5 min of waking), and whether they were a current (someday/every day) or former (no past year/current use) established smoker (≥100 lifetime cigarettes), or an experimental smoker (<100 lifetime cigarettes). Chi-square and multivariable logistic regression analyses examined differences between sexual minority females and heterosexual females on smoking variables. Results: Sexual minority female smokers began smoking regularly at an earlier age and smoked fewer cigarettes per day than heterosexual females. Sexual minority females were more likely to initiate smoking with a menthol cigarette (aOR = 1.27), report past 30-day smoking (aOR = 1.36) and menthol cigarette use (aOR = 1.24) compared to heterosexual females. There were no differences on cigarette dependence. Conclusions: Given the high rates of initiation and current menthol smoking, policies to regulate menthol may decrease smoking disparities for sexual minority females.